2011
DOI: 10.1039/c1nj20202b
|View full text |Cite
|
Sign up to set email alerts
|

A silver-based metal–organic framework material as a ‘reservoir’ of bactericidal metal ions

Abstract: International audienceThe silver-based MOF material Ag3(3-phosphonobenzoate) was evaluated as a bactericidal material. A sustainable release of Ag+, which was quantified by cathodic stripping voltammetry, was responsible for bactericidal activity against the 6 bacterial strains tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 49 publications
3
114
0
4
Order By: Relevance
“…Their rigidity provides some explaination for the production offact that they give rise to thermally stable materials 32 and in few cases non centro-symmetric materials 35 . These organic precursors, which can be synthesised at a multigram scale in 3 steps from the commercially available bromo-benzoic acid, must be also be classified in theas hetero-difunctional compounds in which both functional groups (phosphonic acid, carboxylic acid) can independently be used to connect the organic moiety to an inorganic network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their rigidity provides some explaination for the production offact that they give rise to thermally stable materials 32 and in few cases non centro-symmetric materials 35 . These organic precursors, which can be synthesised at a multigram scale in 3 steps from the commercially available bromo-benzoic acid, must be also be classified in theas hetero-difunctional compounds in which both functional groups (phosphonic acid, carboxylic acid) can independently be used to connect the organic moiety to an inorganic network.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we reported the first example of an efficient bactericidal silver-based hybrid in which phosphonic and carboxylate functional groups tether the organic part with the silver salt in a 3D arrangement. 32 This work was carried out within a context that aimed to study that aimed to examine the use of rigid phosphonic acid derivatives 33 , 34 as building blocks for the construction of crystalline hybrids under hydrothermal conditions to produce fluorescent, 35 thermally stable 36 and non-centrosymmetic materials. 37,38 For Through the study of the construction synthesis of silver-based hybrids we produced materials were produced with which couldthe potentially of acting as a reservoir of silver ions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Jony srebra z nośnika były uwalniane do roztworu, a następnie wykazały działanie przeciwbakteryjne przeciwko badanym szczepom Staphylococcus aureus, Escherichia coli oraz Pseudomonas aeruginosa. Przedłużone uwalnianie jonów o właści-wościach przeciwbakteryjnych otwiera perspektywy na stosowanie BioMOF-ów w preparatach o działaniu miejscowym [28].…”
Section: Mof-y Jako źRódło Metaluunclassified
“…Ponieważ barwnik Br-BODIPY jest kowalencyjnie związany z amino-BDC poprzez wiąza-nie aminowe, jego uwolnienie jest wynikiem degradacji matrycy i dowodzi również uwolnieniu cisplatyny. Badanie kontrolne barwnika niezwiązanego z nośnikiem nie wykazało fluorescencji, co tłumaczy się brakiem zdolności barwnika do przechodzenia przez błonę komórkową i wskazuje, że MIL-101(Fe) jest skutecznym nośnikiem kontrastowego środka optycznego w warunkach in vitro [8,23,28].…”
Section: Mof-y Jako Substancje Kontrastujące W Obrazowaniu Biomedycznymunclassified
“…Silver ion releasing compounds are a well known family of antimicrobials and several silver containing MOF have been reported up to date to this end. Berchel et al reported a silver-based MOF with a 3-phosphonobenzoate ligand that acts as a source of silver ions and showed antibacterial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa [8]. Liu et al reported another silverbased metal-organoboron framework with antibacterial activity against Gram-negative and Gram-positive human pathogens [9].…”
Section: Introductionmentioning
confidence: 98%